Nitrogen fertilizers promote plant growth and assist in manganese (Mn) accumulation by Polygonum pubescens Blume cultured in Mn tailings soil. Issue 12 (15th October 2019) - Yu, Fangming; Li, Yi; Li, Furong; Zhou, Zhenming; Chen, Chaoshu; Liang, Xiaolu; Li, Chunming; Liu, Kehui
Abstract: This study examined how different nitrogen (N) forms and application levels promote plant growth and assist in manganese (Mn) remediation of Polygonum pubescens Blume ( P. pubescens ) cultured in soil with a high Mn level. The effects of ammonium chloride (a) and urea (u), at three application levels (10, 20, and 30 mg L −1 N) and control (no N addition, CK) on the growth, Mn accumulation, and enzymatic anti-oxidative defenses of P. pubescens were examined. In general, both ammonium-N and urea-N promoted the plant mass and height of P. pubescens . The total Mn amount of roots, stems, and leaves in N treatments were higher ( p  < 0.05) than that of CK. The ammonium-N treatments showed greater plant biomass and Mn accumulation compared to the urea-N ones. In general, the accumulations of Mn, Cr, Zn, and Cu were significantly lower ( p  < 0.05) in the N fertilizer treatment than those in the control; while the accumulations of Pb were higher ( p  < 0.05) in P. pubescens across all N fertilizer treatments than those in the control. The N addition decreased the contents of O2 − and H2 O2 in the leaves of P. pubescens, while increasing the activities of enzymatic anti-oxidative defenses.